THE ROLE OF DIGITAL MARKETING FOR BRAND AWARENESS TO IMPROVE MARKETABILITY IN MSMES - Saldin Paputungan; Mohamad Mustaqim Mokoagow; Agus Irianto Paputungan; Sitty Sherihulla Mokoagow; Ervina Kaligis (Jurnal Ekonomi, 2023)
Technological advancements and internet penetration have provided MSMEs with new opportunities to expand their market presence and strengthen their brand position. This phenomenon cannot be separated from the role of digital marketing for micro, small, and medium-sized enterprises (MSMEs) to build brand awareness and interact with customers. Therefore, the purpose of this study is to identify alternative digital marketing options that are effective and relevant for MSMEs in order to build strong brand awareness and increase their competitiveness in an increasingly competitive market.  The research methodology employs a literature review to determine the current trends and developments in digital marketing. Through social media, email marketing, influencer marketing, e-commerce platforms, creative advertising, and the use of video advertising, the findings of this study can provide alternative digital marketing strategies.  By implementing technology, MSMEs will be able to maximize their use of current digital marketing trends in an effort to increase consumer brand awareness of products and to bolster the competitiveness and marketability of MSME products.